2002
DOI: 10.1177/1362361302006003006
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character in Adults with Asperger Syndrome

Abstract: To study the personality characteristics of adults with Asperger syndrome, and investigate the value of self-rating personality inventories, we administered the Temperament and Character Inventory (TCI) to 31 outpatients with Asperger syndrome. The TCI is a self-rating personality inventory that has been validated in the Swedish general population. The results were compared with age- and sex-matched norm groups. Participants with Asperger syndrome scored significantly higher on harm avoidance and lower on self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 13 publications
6
87
0
3
Order By: Relevance
“…For instance, older children with ASDs report experiencing less pleasure from social rewards [557], and social stimuli are relatively less salient for individuals with ASD [558-560]. More generally, individuals with ASD have been found to report lower levels of reward responsivity [561], and behavioral studies have also found evidence for impaired reward learning in individuals with ASD [562]. …”
Section: Reviewmentioning
confidence: 99%
“…For instance, older children with ASDs report experiencing less pleasure from social rewards [557], and social stimuli are relatively less salient for individuals with ASD [558-560]. More generally, individuals with ASD have been found to report lower levels of reward responsivity [561], and behavioral studies have also found evidence for impaired reward learning in individuals with ASD [562]. …”
Section: Reviewmentioning
confidence: 99%
“…Although many want to establish and maintain social relationships, transitional youth with ASD may feel so anxious about the possibility of rejection that they feel compelled to avoid social situations and the possible risk of rejection or social failure. This avoidance may be so severe that these individuals do not even exhibit the initiative and self-directedness to give themselves the necessary exposure to peers or a significant chance to succeed (Anckarsäter et al, 2006;Ozonoff et al, 2005;Soderstrom et al, 2002). Low social functioning and anxiety in social relationships tends to carry over to romantic relationships in adolescents and adults with ASD (Stokes et al, 2007).…”
Section: Mental Healthmentioning
confidence: 99%
“…Individuals with ASD generally feel more comfortable with rigid routines and restricted www.intechopen.com interests, and may resist change (Frith, 2004;Ozonoff et al, 2005). From childhood and throughout adulthood they may remain averse to seeking new experiences and, unlike neurotypical peers, become more motivated by fear of failure or other dangers than approaching the possibility of success or another reward (Anckarsäter et al, 2006;Schwartz et al, 2009;Soderstrom et al, 2002;South et al, 2011). By adolescence they may blame themselves for social or other disappointments and develop learned helplessness (Barnhill, 2001;Barnhill & Myles, 2001).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations